Magnetic resonance imaging and spectroscopy for differential assessment of liver abnormalities induced by Opisthorchis felineus in an animal model - Pershina A. G. Aleksandra Gennadievna; Ivanov V. V.; Efimova L. V. Lina Viktorovna; Shevelev O. B. Oleg; Vtorushin S. V. Sergey; Perevozchikova T. V. Tatjana; Sazonov A. E. Alexey; Ogorodova L. M. Lyudmila Mikhaylovna (2017, 2017)
Title screen